Implementasi Kurikulum Al-Islam dan Kemuhammadiyahan dalam meningkatkan Kadar Religiusitas Siswa SMK Muhammadiyah 2 Sragen Tahun Ajaran 2014/2015 - Maulana, Fajrin, Dr. Badaruddin, M.Ag, Dr. Waston, M.Hum (2016)
This research is motivated by the gap between expectation and reality that occurs in SMK Muhammadiyah 2 Sragen. Hope in question is the vision of SMK Muhammadiyah 2 Sragen that produce human resources who have faith and piety, virtuous, and master technology so it can compete in the free market era. In fact, the behavior of the majority of students in these schools do not yet reflect the faith and piety as aspired by SMK Muhammadiyah 2 Sragen. The problem in this research is "How Curriculum Implementation Al-Islam and Kemuhammadiyahan and Like What Forms Increased Levels of Religiosity Students at SMK Muhammadiyah 2 Sragen In 2014/2015 Academic Year?" The purpose of this study is to describe the implementation of the curriculum al-Islam and Kemuhammadiyahan as well as other forms of enhancing the level of religiosity of students in SMK Muhammadiyah 2 Sragen in the academic year 2014/2015. The research is a qualitative research with descriptive approach. The location of this research is SMK Muhammadiyah 2 Sragen. Data was collected through interviews, observation and documentation. Data analysis method used is the inductive method. The stages of data analysis include data reduction, data presentation and conclusion. Implementation of research results Curriculum Al-Islam and Kemuhammadiyahan in Improving Levels of Religiosity Students at SMK Muhammadiyah 2 Sragen the Academic Year 2014/2015, among others: (1) Implementation of Curriculum Al-Islam and Kemuhammadiyahan terms of development program implementation procedures are in accordance with the curriculum of 2013. (2) Implementation of Curriculum Al-Islam and Kemuhammadiyahan terms of learning implementation, largely meets the criteria-based learning curriculum implementation, 2013. (3) Implementation of Curriculum Al-Islam and Kemuhammadiyahan terms of evaluation of learning, still not in accordance with the standards of evaluation in curriculum 2013. This is because evaluations of teachers only limited to the domain of learning outcomes. As for the evaluation of the attitude during the learning aspect is still not implemented. (4) The result of elevated levels of religiosity of students in SMK Muhammadiyah 2 Sragen based on the data collected, it is known that increased levels of religiosity of the most prominent are the ideological dimension, ritual dimension, the dimension of knowledge, experience and appreciation of the religious dimension. As if the consequences in terms of dimensions, it has not found any significant improvement.